Interactive Quizzes and Game Mechanics to Increase Engagement, Motivation, and Retention in Online English Learning Platforms - Singgih Prastawa; Yanuar Triadi; Dedi Gunawan Saputra (Global Education : International Journal of Educational Sciences and Languages, 2024)
The rapid growth of online English learning platforms has introduced new opportunities for language acquisition, yet maintaining student engagement and motivation remains a persistent challenge. Many learners experience reduced participation and limited knowledge retention in digital settings compared to traditional classroom environments. Addressing this issue, the present study investigates the effectiveness of gamified quizzes as a pedagogical strategy to enhance engagement, motivation, and retention among online English learners. A quasi-experimental design was employed with two groups: a control group that used a standard online platform and a treatment group that engaged with gamified quizzes incorporating points, badges, and leaderboards. Data on engagement were collected through participation frequency and time spent, while motivation was measured using pre- and post-intervention questionnaires, and retention was assessed through follow-up tests. Statistical analyses using independent-sample t-tests and ANOVA revealed significant differences between the two groups. The treatment group demonstrated higher engagement, stronger motivation, and improved retention outcomes compared to the control group. These results, supported by both tabular and graphical representations, highlight the pedagogical value of gamification in addressing motivational challenges and fostering meaningful learning. The study concludes that gamified quizzes serve not only as motivational tools but also as effective mechanisms to strengthen long-term knowledge retention in online English education. Implications for practice suggest that educators and digital learning designers should integrate gamification elements as a central feature of online platforms to optimize learner outcomes.